Relationship between Malaysian Plover occurrence and coastal vegetation at Pantai Tanjung Resang, Mersing, Johor - Theventhiram, Yogasunthari (2019)
The Malaysian Plover, Charadrius peronii is a threatened shorebird species found in Southeast Asia and mostly at the southwest coast of Peninsular Malaysia. A sandy beach and coastal vegetation is a crucial habitat for the shorebird. This study aimed to assess the influence of coastal vegetation and other environmental variables on the Malaysian Plover occurrence at Pantai Tanjung Resang, Mersing, Johor. Point sampling was conducted from July to early of August, 2018. Based on logistic regression model, only vegetation cover was statistically significant in influencing the Malaysian Plover occurrence (p=0.014) compared to other variables. Increasing vegetation cover was associated with a decrease in the occurrence of Malaysian Plover. Breeding location and environment variables were counted not statistically correlated due to a low number of breeding Malaysian plovers. However, this study found that breeding pairs were preferred vegetation cover of at least 76% even though the relationship was non-significant. Results from this study showed that vegetation cover is an essential habitat factor for the Malaysian Plover.